Gambaran umum lokalisasi pasar Kembang sebagai pengembangan komunitas perempuan pekerja seks - Agatha Astri Ratnasari; Fitrina Mahardani Kusumaningrum; Yanri Wijayanti (Berita Kedokteran Masyarakat (BKM), 2019)
General description of Pasar Kembang localization as a community development of female sex workersPurpose: To find out a general description of the localization of Pasar Kembang as a community development for female sex workers. Method:This research is a qualitative descriptive study. The research informants were 7 female sex workers who were selected by purposive sampling. Results:The Community of Bunga Seroja as a community of female sex workers in Pasar Kembang localization strives to develop this community in an effort to fulfill the health and welfare of female sex workers. The organization of this community is not optimal because of the lack of resources in community management. Empowerment activities and sustainability program are important elements on the development of a community of female sex workers. Conclusion:The Community of Bunga Seroja is a place for female sex workers in organization; the implementation of community development not optimal due to limited resources; participation, empowerment, and sustainability are important elements in the development of female sex workers group by the Community of Bunga Seroja.